PENGEMBANGAN MEDIA BOLPIN (BOLA PINTAR) PADA PEMBELAJARAN KOOPERATIF STAD (STUDENT TEAM ACHIEVEMENT DIVISIONS) MATA PELAJARAN IPA KELAS III SEKOLAH DASAR - Asep Sahal Tamhida (Universitas Negeri Medan, 2018)
Abstract : Development of Bolpin Media (Smart Ball) in Cooperative Learning STAD (Student Team Achievement Divisions) Science Class III Subjects in Elementary School. The purpose of this research is to know the development of Bolpin media (Bola Pintar) on cooperative learning of STAD (Student Team Achievement Division) of Science Class III subjects in Elementary School. This research is a research and development research population of SDN Pringsari 02, SDN Bendungan, and SDIT Cahaya Umat Samples taken are third grade students of SDN Pringsari 02, SDN Bendungan, and SDIT Cahaya Umat The data in this research obtained from documentation, observation, interview, and questionnaire Based on the results of this research can be stated, The development of Bolpin media products (Bola Pintar) on STAD cooperative learning (Student Team Achievement Divisions) based on indicators of achievement of basic competencies in subjects in grade III Primary School.Keywords : Bolpin Media (Smart Ball), Cooperative Learning, STAD (Student Team Achievement Divisions)Abstrak : Pengembangan Media Bolpin (Bola Pintar) pada Pembelajaran Kooperatif STAD (Student Team Achievement Divisions) Mata Pelajaran IPA Kelas III di Sekolah Dasar. Tujuan yang hendak dicapai dalam penelitian ini adalah untuk mengetahui pengembangan media Bolpin (Bola Pintar) pada pembelajaran kooperatif STAD (Student Team Achievement Divisions) mata pelajaran IPA Kelas III di Sekolah Dasar. Jenis penelitian ini adalah penelitian dan pengembangan (Research and Development. Populasi penelitian adalah SDN Pringsari 02, SDN Bendungan, dan SDIT Cahaya Umat. Sampel yang diambil adalah siswa kelas III SDN Pringsari 02, SDN Bendungan, dan SDIT Cahaya Umat. Data dalam penelitian ini diperoleh dari dokumentasi, observasi, wawancara, dan angket. Berdasarkan hasil penelitian ini dapat dikemukakan, Pengembangan produk media Bolpin (Bola Pintar) pada pembelajaran kooperatif STAD (Student Team Achievement Divisions) berdasarkan indikator pencapaian kompetensi dasar pada mata pelajaran di kelas III Sekolah Dasar.Kata Kunci : Media Bolpin (Bola Pintar), Pembelajaran kooperatif, STAD (Student Team Achievement Divisions)